Limited Liability Partnership (LLP@PLT): new business vehicle for the Malaysian legal and accounting private practice - Abdul Rahman, Nasarudin; Abd Ghadas, Zuhairah Ariff; Salleh, Kamaliah; Abd Rahman, Hussin Mohamed (UPM Press, 2015)
Prior to 2012, the business practice and legal frameworks in Malaysia were primarily carried out in the form of sole proprietorships, partnerships and registered company. However, with the development of the economy, the general partnership structure was found to be no longer suitable for some of businesses, particularly professional ones. The rising cost of conducting trade and litigation has forced partners to take precautions with regards to liabilities connected with doing business. This led to the introduction of limited liability partnership (LLP). In Malaysia, the Limited Liability Partnership (LLP) Act was enacted in February 2012; it introduced a new business vehicle in the local market. LLPs are seen as alternative business vehicles for professionals in Malaysia who are not allowed to carry out business in the form of companies, namely lawyers and accountants. Such restriction is provided by the professional’s regulatory body such as the Bar Council and the Malaysian Institute of Accountants. With the introduction of LLP, these two professions are allowed to enjoy quasi limited liability by carrying out their private practice in the form of LLP. This paper discusses the legal framework of Malaysian LLP and how it is useful for the legal and accounting private practice.